2002
DOI: 10.1021/ed079p239
|View full text |Cite
|
Sign up to set email alerts
|

Deaf Students, Teachers, and Interpreters in the Chemistry Lab

Abstract: This report describes an undergraduate research program at James Madison University that includes deaf and hard-of-hearing students from Gallaudet University, deaf teachers from schools for the Deaf, and both professional interpreters and students engaged in sign language interpreter training. Methods used over a three-year period to maximize participation and expand research opportunities for the students, teachers, and interpreters are shared with the hope that similar projects might be encouraged and replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This project also focused the teacher, mainly future teachers for the Deaf. In addition to the difficulty found in teaching science to small children (Tilgner, 1990) it has been reported that there is a need for more science teachers in secondary schools and that this is more severe when it involves science teachers in deaf schools (Seal, Wynne, & MacDonald, 2002;Mangrubang, 2005). The Gallaudet University also sought to create a training course for science teachers for the Deaf using an inquiry-based course (Mangrubang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This project also focused the teacher, mainly future teachers for the Deaf. In addition to the difficulty found in teaching science to small children (Tilgner, 1990) it has been reported that there is a need for more science teachers in secondary schools and that this is more severe when it involves science teachers in deaf schools (Seal, Wynne, & MacDonald, 2002;Mangrubang, 2005). The Gallaudet University also sought to create a training course for science teachers for the Deaf using an inquiry-based course (Mangrubang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We considered RSCU as an opportunity to educate ourselves, cultivate inclusivity within the field of chemistry, and encourage participants to examine their own behaviors and biases. Therefore, each meeting included a short presentation by a RSCU faculty participant on DEI-related issues, such as the demographics of STEM fields, bias and disparities in hiring and funding, accessibility of laboratories for people with disabilities, , and bias in standardized tests. , As with the research seminars, a journal article or editorial related to the DEI subject was shared with participants to read in advance of the meeting. , …”
Section: Description Of Supergroupmentioning
confidence: 99%
“…[Grundy and McGinn 2008] describes a hard-of-hearing graduate student's experience; [Huenerfauth 2010] describes the experience of a group that involved deaf undergraduate and high school students in ASL animation research through the City University of New York; [MacDonald et al 2002] describes James Madison University's undergraduate research program in chemistry, which involves deaf and hard-of-hearing students. Finally, for a description of some of the benefits that have been shown for members of underrepresented groups who do undergraduate research, see [UROP 2012;Hathaway et al 2002].…”
Section: Further Readingmentioning
confidence: 99%